PERAN INFORMASI KELUARGA BERENCANA PADA PERSEPSI DAN PARTISIPASI MASYARAKAT DALAM PRAKTEK KB (Kasus di Desa Rengas Abang Kecamatan Air SugihanKabupaten Ogan Komering Ilir Provinsi Sumatera Selatan) - Badrun Munandar (Jurnal Dosen Universitas PGRI Palembang)
ABSTRAKThe current political reform led to a paradigm shift in the implementation of family planning programs that are highly dependent on strategic policy position holders in the area. The purpose of this study was to determine the resources that provide family planning information to the public 1 , differences in perception according to resources 2 , participation by the perception of differences 3 , differences in participation according to resources 4 , and to determine differences in participation according to the perception which is controlled by the level of education, number of children as well as the desire to have more children 5 . The method used in this research is census. Data analysis was done by chi-square test using the program SPSS version 17.0.The results showed that most respondents obtain family planning information via television (58.2%), and there is the influence of the information on perception and participation of family planning. This is evidenced bythe differences in perception according to information exposure, according to the perception of participation and participation by exposure information convincingly with 95% confidence level. In the control variables there are differences in the level of participation in education and number of children conclusively (95%), while participation by the desire to have more children there are no significant differences.Information decisive participation in the practice of family planning, but did not specify in its desire to have more children. This is because the perception of the value of different children, so the desire to have more children does not affect the participation in the practice of family planning.Keywords: Information, Perception, Participation, Family Planning